2001
DOI: 10.1097/00000658-200110000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgical Training in an Academic Institution

Abstract: ObjectiveTo detail robotic procedure development and clinical applications for mitral valve, biliary, and gastric reflux operations, and to implement a multispecialty robotic surgery training curriculum for both surgeons and surgical teams. Summary Background DataRemote, accurate telemanipulation of intracavitary instruments by general and cardiac surgeons is now possible. Complex technologic advancements in surgical robotics require well-designed training programs. Moreover, efficient robotic surgical procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(117 citation statements)
references
References 29 publications
(19 reference statements)
1
112
0
4
Order By: Relevance
“…The first RC was performed by Belgian Jacques Himpens in 1997, marking the first human use of the da Vinci ® surgical system (21). Since then, several studies have demonstrated that RC is safe and effective for general surgeons in the early part of their learning curve for robotic surgery (22,23). The learning curve for RC varies widely, ranging from a mean surgical time of 57-167 minutes (24).…”
Section: Robotic Cholecystectomy As a Tool For Trainingmentioning
confidence: 99%
“…The first RC was performed by Belgian Jacques Himpens in 1997, marking the first human use of the da Vinci ® surgical system (21). Since then, several studies have demonstrated that RC is safe and effective for general surgeons in the early part of their learning curve for robotic surgery (22,23). The learning curve for RC varies widely, ranging from a mean surgical time of 57-167 minutes (24).…”
Section: Robotic Cholecystectomy As a Tool For Trainingmentioning
confidence: 99%
“…The follow-up was done during a patient's visit to the attending physician and/ or telephone interview. The patient's evaluation was obtaining using a visual analog score (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Approval by our local Ethics Committee was obtained prior to carrying out this study.…”
Section: Methodsmentioning
confidence: 99%
“…En 2003 otro estudio realizado por el mismo grupo reveló que aunque el 57% de los residentes de cirugía mostraba interés por la cirugía robótica, la mayoría (80%) no contaba con un programa de formación en cirugía robótica en las instituciones en que estudiaba 28 . Son pocos los centros académicos que han desarrollado una didáctica formal que enseñe a los alumnos a practicar este tipo de cirugía 29 .…”
Section: Cirugía Robótica Y Formaciónunclassified